COMPREHENSIVE REVIEW OF EPIDEMIOLOGICAL OBSERVATIONAL TECHNIQUES IN ASSESSING DATA COLLECTION METHODS, ANALYSIS APPROACHES, AND REPORTING SYSTEMS FOR PUBLIC HEALTH SURVEILLANCE - Alhassan Saleh Hadi Almuhamidh, Bandar Saeed Alawadh, Mohammed Abbasi Alrbah, Mohammed Ali Hussein Al Ofair, Kuzman Nasher Mohammed Kuzman, Hadi Saleh Hadi Almahmeed, Yasir Hayyan Omaysh Alwadai, Ali Mohammed Hamed Alyami (Chelonian Research Foundation, 2023)
Epidemiological observation is used in the first place in public health surveillance, which perceives important tips for the status of diseases, risk factors, health of the population, and trends. Here, the review covers all the techniques of data collection, methods of analysis, reporting systems, etc., that are used for public health surveillance in epidemiological observation. While the literature review and empirical analysis in this study identify the strengths, weaknesses, and emerging trends in observational techniques, the summaries then present the strengths, weaknesses, and emerging trends in this area. Data analysis indicates the necessity of highly innovative data collection techniques, advanced analytics, and rightful reporting to strengthen institutional efforts. Suggestions for the improvement of observational tactics in public health research practice are provided in order to guide further improvement in this field. Keywords: epidemiology, astronomical observations, data collection, analysis procedures, public health information analysis, disease surveillance. Exercise.